Trends in ICT Development - Gulnara Abdrakhmanova; Galina Kovaleva (Foresight and STI Governance)
The paper highlights the tendencies of information and communication technologies in Russia based on the data of information society statistics. The authors analyze the factors of development of information and communication technologies, expenses placed upon them and the efficiency of their usage. Along with some positive tendencies such as appearance of new forms of service and organizational innovations in production, the paper also covers the problems of applying these technologies into practice.